Persepsi dan preferensi kenyamanan pejalan kaki tunanetra terhadap jalur pedestrian di Jalan Panglima Besar Sudirman, Kota Denpasar - Sa’adah, Titin Maghfirotus; Kohdrata, Naniek; Semarajaya, Cokorda Gede Alit (Jurnal Arsitektur Lansekap, 2018)
Blind pedestrian perception and preference of comfort at pedestrian walkway at Panglima Besar Sudirman Street, Denpasar City. The main problem for the blind is limited public facilities in Indonesia. Denpasar is the capital province of Bali, so the need of physical infrastructure is very important. The aim of this research was to identify and evaluate the existing condition of the pedestrian path that is related to the comfort aspect, and to know the perception and preference of the blind pedestrian user to the comfort of the pedestrian path at Jalan P. B Sudirman Denpasar, and to recommend the accessibility model as supporting the needs and rights for those blind people. The research method were survey method with observation technique, questionnaires, and literature study. The inconsistency of pedestrian size and elevation between 15 – 35 cm of one of the causes of pedestrian walkway was considered unfit for use by the disadvantage people, thus the pedestrian lane space scenario at Jalan P. B Sudirman Denpasar is to make the pedestrian path as a mobilization path that is easily accessible to everyone and optimally in its utilization. The results of this study are expected to be a consideration for the parties concerned in the related development.